PENGARUH KONDISI LINGKUNGAN TERHADAP SERANGAN PENGGEREK KAYU DI LAUT - Mohammad Muslich; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1988)
One hundred  and  twenty   five pieces  of  wood  from  five  species had been exposed  to Marine Borers in five different locations.  The test sites chosen  were around  Gulf of Jakarta,  i.e.  about  3 km  off  shore in Mauk, Mauk estuary,  Tanjung Pasir shore,  Rambut  Island  and Puntung  Java Island.The  result shows  that  at  the sea site  where the salinity  is relatively stable around  29‰  -   30‰  and at the Rambut  and Puntung Java Islands  30‰  -   34‰, all of  the  wood  tested  are badly  attacked by Marine Borers.  The result also shows  that  at  the  Mauk  estuary  and  Tanjung  Pasir shore  where  the salinity  5°/oo  -  30°/oo, damage  is only  small